PENGARUH LINGKUNGAN RUMAH TERHADAP ISPA BALITA DI WILAYAH KERJA PUSKESMAS TANJUNG HALOBAN KABUPATEN LABUHAN BATU TAHUN 2017 - Dessy Irfi Jayanti; Taufik Ashar; Destanul Aulia (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ISPA (Upper Respiratory Tract Infection) is an environment-based disease and one of the major causes of the morbidity and mortality of communicable diseases in the world. WHO states that almost four million people die from ISPA every year; 98% of them were caused by lower respiratory tract infection. The rate of mortality is high in babies, children and adults. The objective of the research was to discover the influence of home physical environment, pollutant source and family characteristics on ISPA in balita. This is an analytical survey research with cross sectional research design. The population was all balita i.e. 200 children and 65 of them were taken as the samples non-randomly. Chi-square testing and multiple logistic regression testing were employed for the data analysis. The results of the research demonstrated that ventilation, lighting and smoking history had significant influence on the prevalence of ISPA in balita. Meanwhile, occupancy density did not have any influence on the prevalence of ISPA. The results of the multiple logistic regression testing showed that smoking history was the variable with the most dominant influence on the prevalence of ISPA with p value 0,003, PR=11,517;95% CI=2,360-56,198, which indicated that the respondents with smoking history had 11,517 times higher risk of ISPA in balita compared to the respondents without smoking history. It is suggested that the Puskesmas (Public Health Center for sub district level) improve the counseling about health especially information related to ISPA, so that it can reduce the prevalence of ISPA or other disease in balita. Keywords:    ISPA, Home Environment, Under Five Year Old Children, Smoking History